Uji Mutagenisitas dan Anti Kanker Ekstrak Aseton Dan N-Heksana Dari Kulit Batang Sesoot (Garcinia picrorrhiza Miq.) - Radji, Maksum; Sumiati, Atiek; Indani, Nuning (UI Scholars Hub, 2004)
Mutagenicity and anti-mutagenicity of the acetone and n-hexane extracts of Garcinia picrorrhiza Miq.bark have been studied by Ames method using Salmonella typhimurium TA 97, TA 98 TA 100, TA 102, dan Escherichia coli WP2. The results showed that the two extracts had a positive effect. It can be concluded that the acetone and n-hexane extracts of Garcinia picrorrhiza Miq. bark have anticancer activity.